2021
DOI: 10.7150/jca.53824
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of conversion therapy on initially unresectable locally advanced rectal cancer

Abstract: Background and purpose: Research on the efficacy of conversion therapy for initially unresectable mid-low rectal cancer (IURC) remained limited. This study aimed to assess the efficacy and safety of the conversion regimen for IURC and analyze the long-term outcomes of these patients. Methods: We retrospectively analyzed the data of clinically diagnosed IURC patients who received conversion therapy between October 2010 and April 2017. The conversion therapy consisted of long-term radiation, concurrent chemother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Interventional treatments, targeted drugs, and immunotherapy have been demonstrated as potential forms of TC in gastric and colon cancer. Liu et al 6 used chemotherapy combined with radiotherapy as a conversion therapy to treat 61 patients with unresectable rectal cancer and reported 51 patients with R0 resection with a conversion rate of 83.6%. Besides, several studies have also demonstrated favorable outcomes to conversion therapy in patients with stage IV gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Interventional treatments, targeted drugs, and immunotherapy have been demonstrated as potential forms of TC in gastric and colon cancer. Liu et al 6 used chemotherapy combined with radiotherapy as a conversion therapy to treat 61 patients with unresectable rectal cancer and reported 51 patients with R0 resection with a conversion rate of 83.6%. Besides, several studies have also demonstrated favorable outcomes to conversion therapy in patients with stage IV gastric cancer.…”
Section: Introductionmentioning
confidence: 99%